Compressive strength of storey height burnt clay brick masonry walls - Gumaste, K.S.; Rao, K.S. Nanjunda; Reddy, B.V. Venkatarama; Jagadish, K.S. (Journal of Structural Engineering, 2024)
The compressive strength of storey height walls constructed with two types of burnt clay bricks and two types of mortars with stretcher bond and English bond are presented in this paper. The strength of the walls has been compared with the strength of smaller sized masonry wallettes. The strength of the walls have been compared with the permissible compressive stress in masonry as per IS 1905-1987¹. The failure mechanism of stretcher bond walls has been compared with English bond masonry wall. It is observed that stretcher bond masonry is stronger than English bond masonry. The permissible compressive stress specified in IS 1905-1987 appears to be conservative with factor of safety more than 3. It is observed that the stretcher bond walls due to their higher slenderness ratio have failed under combined action of inplane compression and out-of-plane bending whereas the English bond wall has failed due to material (brick) crushing and diagonal shear with splitting of the wall into two wythes through the thickness of the wall.